2016
DOI: 10.1080/13102818.2016.1170631
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment in middle-aged patients with diabetes

Abstract: Most studies focus on elderly patients with type 2 diabetes mellitus (T2DM). There is little known about the hearing of middle-aged subjects with T2DM. The objective of this study is to evaluate hearing impairment in patients aged 40À50 years with T2DM using pure-tone audiometry and high-frequency audiometry. Forty patients with T2DM (19 males, 21 females) and 40 (20 males, 20 females) age and sex similar controls were included. All subjects completed clinical, laboratory and auditory assessments. Pure-tone au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…4 The probability of hearing loss in patients with diabetes is twice as high as in healthy people suggesting hearing loss as a complication of diabetes. 14 In this study, the mean hearing threshold was significantly higher at 4000 Hz and 8000 Hz in diabetic patients with the duration of diabetes for more than 5 years. According to Ozkurt FE et al, it takes at least 5 years after the diagnosis of diabetes to show the effect on hearing threshold.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…4 The probability of hearing loss in patients with diabetes is twice as high as in healthy people suggesting hearing loss as a complication of diabetes. 14 In this study, the mean hearing threshold was significantly higher at 4000 Hz and 8000 Hz in diabetic patients with the duration of diabetes for more than 5 years. According to Ozkurt FE et al, it takes at least 5 years after the diagnosis of diabetes to show the effect on hearing threshold.…”
Section: Discussionmentioning
confidence: 46%
“…According to Ozkurt FE et al, it takes at least 5 years after the diagnosis of diabetes to show the effect on hearing threshold. 14 On contrary to these findings, the studies done in India reported that the duration of diabetes had no impact on the hearing threshold in diabetic patients. 1,13 It is postulated that the duration of poor glycemic control is more important than the duration of diabetes mellitus itself.…”
Section: Discussionmentioning
confidence: 89%